Mactanamide and lariciresinol as radical scavengers and Fe2+ ion chelators – A DFT study. (December 2022) - Amić, Ana; Cagardová, Denisa Mastiľák
Abstract: A DFT based kinetic study of OOH radical scavenging potency of mactanamide (MA) and lariciresinol (LA), two natural polyphenols, indicates their nearly equal potential via the proton coupled electron transfer (PCET) mechanism in lipid media. Contribution of C–H bond breaking to this potency is negligible compared to O–H bond breaking, contrary to recent claims. The predicted potency of both compounds is not sufficient to protect biological molecules from oxidative damage in lipid media. In aqueous media, the scavenging potency of MA and LA phenoxide anions via the single electron transfer (SET) mechanism is much higher and may contribute to the protection of lipids, proteins, and DNA from OOH radical damage. Also, MA and LA have the potential to chelate catalytic Fe 2+ ions, thus suppressing the formation of dangerous OH radicals via Fenton-type reactions. The monoanionic species of MA and LA show stronger monodentate chelating ability with Fe 2+ ion compared to its neutral form. The dianionic specie LA 2− exhibited the highest chelation ability with Fe 2+ ion via bidentate 1:2 coordination. However, direct radical scavenging and metal chelation could be rarely operative in vivo because MA and LA presumably achieve very low concentrations in systemic circulation. Graphical abstract: Kinetic analysis indicates that radical scavenging proceeds via phenolic O–H bond breaking. Contribution of C–H bond cleavage is negligible. Anionic species chelate Fe 2+ ions effectively. Image 1 Highlights: Mactanamide (MA) and lariciresinol (LA) .OOH radical scavenging potency was studied. Kinetic analysis indicates O–H bond breaking as much faster than C–H bond breaking. In lipidic media, MA and LA have no potential to suppress .OOH radical damage. In water, their phenoxide anions may protect biological molecules from oxidative damage. Phenoxide anions of MA and LA in water have potential to chelate catalytic Fe 2+ ion.